Ултрасонографски промени и функционални бубрежни нарушувања кај адултни пациенти кои во детската возраст биле дијагностицирани со везикоуретерален рефлукс (ВУР) - Бундовска Коцев, Смиљана (Медицински факултет, УКИМ, Скопје, 2019)
Background. Triad of childhood vesicoureteral reflux (VUR), urinary infection (UTI) and renal scarring might initiate potentially serious consequences that lead to renal dysfunction manifested at the second or third decade of life. Objective. To identify the risk factors predictive for renal dysfunction in adults with primary VUR after long-term follow-up. Methods. In this retrospective-prospective study we evaluated the records of 101 children (94.1% female, 5.9% male) at median age of 5.2 ± 2.3 years (1-12 years), suffering from UTI and VUR. Тo evaluate the presence of parenchymal lesions, renal scintigraphy with Technetium-99m dimercaptosuccinic acid (DMSA scan) was used. The following medical variables from the children medical documentation were obtained: sex, age of primary VUR diagnosis, VUR grade, unilateral or bilateral VUR, previous UTI, presence and localization of renal scars (uni- or bilateral) and a method of treatment (conservative, surgical or endoscopic). The patients were interviewed after mean of 21 years from the first episodes of VUR (from 8 to 32 years). The history and physical examination was done and included height and weight as well as blood pressure measurement. Images of kidneys/urinary tract and an estimate of kidney size and / or existence of disorders were determined using ultrasonography (Siemens Acuson X 300). Renal function was determined from the estimated glomerular filtration rate (eGFR). Results. The grade of the VUR was on average 2,89 ± 0,80 degrees, which is, a minimum of a second and a maximum of a fifth degree, but the third degree was most commonly reported. Renal scars were detected in 68.3% of the total of 82 patients, and scarring on both kidneys was observed in 7.3% of patients. Long-term follow-up of these patients showed that the ultrasonographic finding was normal in most patients. The most commonly reported abnormalities were: a smaller kidney, irregular contour of the kidney parenchyma, or dilatation of the channel system. The risk of renal scarring on both kidneys increases by about 4.7 times the grade of VUR. A grade II or III VUR was with a sensitivity of 83.3% and a specificity of 51.9% in prediction of the presence of scarring on both kidneys. Arterial hypertension following long-term follow-up of patients with primary VUR in this study was established only in one patient. Proteinuria was observed in 13.9% of patients. Significant values ( ³ 20 mg / L) of albuminuria determined by deep-stick were observed in 14.1% of thr patients, and increased albumin/creatinine ratio in the urine was found in 9.9% of the patients. Complications in pregnancy (proteinuria and preeclampsia) occurred in 16.7% of 30 realized pregnancies, significantly more often in those with reflux nephropathy. Linear regression analysis revealed that presence of proteinuria (B=-33,7, p=0.0001), the greater number of years from VUR diagnosis (B=-1.6, p=0,002) and renal scarring (B=-14,8, p=0.005) appeared as independent predictors of reduced global eGFRcreat. The same variables plus microalbuminuria (B=-1.0, p=0.012) appeared as independent predictors of reduced global eGFRcreat-cys. Bilateral scarring (OR=25.5. p=0.003) appeared as independent predictor of greater risk for CKD assessed using eGFRcreat while greater number of years from VUR diagnosis (OR=1.7, p=0.092), microalbuminuria (OR=1.3, p=0.047) and again bilateral scarring (OR=31.3, p=0.040) appeared as predictors of risk for CKD assessed using eGFRcreat-cys. Conclusion. Identification of those patients with increased risk of progression to CKD should be the goal in all patients with childhood VUR. Continuity and optimal transition of patients from pediatric to adult nephrological care and monitoring are required.
Докторска дисертација одбранета во 2019 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Дафина Кузмановска.
Keywords: Childhood vesicoureteral reflux, renal dysfunction, chronic renal failure, predictive risk factors